Pelaksanaan Program Pendidikan Kecakapan Wirausaha dalam Meningkatkan Pendapatan Warga Belajar Kursus Tata Boga di SKB Mojoagung - Khoirunnisa, Fitri; Artha, I Ketut Atmaja Jhony (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This study aims to (1) describe the implementation of the entrepreneurship skills education program in increasing the income of learners (2) identify the indicators in the implementation of the entrepreneurship skills education program in increasing the income of learners. The research method used is qualitative using in-depth interview data collection techniques, observation, and documentation. The entrepreneurship skills education program is conducted to improve the standard of living of the community through education and training. There are criteria for learners of this program, namely individuals aged 17-25 years old, not currently attending school or employed, to participate in the entrepreneurship skills education program in increasing the income of learners by enhancing skills, acquiring new knowledge, forming an entrepreneurial mindset in an effort to become graduates capable of establishing and managing independent businesses. The results of this study indicate that the implementation of the entrepreneurship skills education program has five indicators: instructors, learners, materials, methods, and objectives. In increasing the income of learners, there are four indicators: improving skills, entrepreneurial spirit, increasing income, and improving welfare. The entrepreneurship skills education program implemented is through enhancing skills and acquiring knowledge in the form of entrepreneurship education and culinary courses.